Gallant by Bold: final year degree online exhibition bachelor of Graphic Design class of 2021: multimedia / Fakulti Seni Lukis & Seni Reka UiTM Shah Alam - Universiti Teknologi MARA, Fakulti Seni Lukis & Seni Reka (Fakulti Seni Lukis & Seni Reka UiTM Shah Alam, 2021)
Multimedia is a form of communication that integrates various content forms, such as text, audio, video, graphics, and animation at the same time.